Pro-inflammatory Monocyte Phenotype During Acute Progression of Cerebral Small Vessel Disease - Noz, Marlies P.; Telgte, Annemieke ter; Wiegertjes, Kim; Tuladhar, Anil M.; Kaffa, Charlotte; Kersten, Simone; Bekkering, Siroon; van der Heijden, Charlotte D. C. C.; Hoischen, Alexander; Joosten, Leo A. B.; Netea, Mihai G.; Duering, Marco; et al. (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background The aetiology of cerebral small vessel disease (SVD) remains elusive, though evidence is accumulating that inflammation contributes to its pathophysiology. We recently showed retrospectively that pro-inflammatory monocytes are associated with the long-term progression of white matter hyperintensities (WMH). In this prospective high-frequency imaging study, we hypothesize that the incidence of SVD progression coincides with a pro-inflammatory monocyte phenotype. Methods Individuals with SVD underwent monthly magnetic resonance imaging (MRI) for 10 consecutive months to detect SVD progression, defined as acute diffusion-weighted imaging positive (DWI+) lesions, incident microbleeds, incident lacunes, and WMH progression. Circulating inflammatory markers were measured, cytokine production capacity of monocytes was assessed after ex vivo stimulation, and RNAsequencing was performed on isolated monocytes in a subset of participants. Results 13 out of 35 individuals developed SVD progression (70±6 years, 54% men), based on incident lesions (n=7) and/or upper quartile WMH progression (n=9). Circulating E-selectin concentration (p<0.05) and the cytokine production capacity of IL-1β and IL-6 (p<0.01) was higher in individuals with SVD progression. Moreover, RNAsequencing revealed a pro-inflammatory monocyte signature including genes involved in myelination, blood-brain-barrier and endothelial-leukocyte interaction. Conclusions Circulating monocytes of individuals with progressive SVD have an inflammatory phenotype, characterised by the increased cytokine production capacity and a pro-inflammatory transcriptional signature.